Sex differences in eating related behaviors and psychopathology among adolescent military dependents at risk for adult obesity and eating disorders. (April 2019) - Quattlebaum, Mary; Burke, Natasha L.; Higgins Neyland, M.K.; Leu, William; Schvey, Natasha A.; Pine, Abigail; Morettini, Alexandria; LeMay-Russell, Sarah; Wilfley, Denise E.; Stephens, Mark; Sbrocco, Tracy; Yanovski, Jack A.; et al.
Abstract: Stressors unique to military families may place dependents of military service members of both sexes at high-risk for disordered-eating. Yet, there are no data examining sex-related differences in eating pathology and distress among this population. Therefore, we examined disordered-eating attitudes and associated psychosocial characteristics in adolescent military dependents at high-risk for both eating disorders and adult obesity (i.e., BMI ≥ 85th percentile and elevated anxiety symptoms and/or loss-of-control eating). One-hundred-twenty-five (55.2% female) adolescent (12–17 y) military dependents were studied prior to entry in an eating disorder and obesity prevention trial. Youth were administered the Eating Disorder Examination interview to determine disordered-eating attitudes, and completed questionnaires to assess self-esteem, social functioning, and depression. Girls and boys did not differ in BMI z ( p  = .66) or race/ethnicity ( p  = .997/ p  = .55). Adjusting for relevant covariates, girls and boys did not differ significantly with regard to disordered-eating global scores ( p  = .38), self-esteem ( p  = .23), or social functioning ( p  = .19). By contrast, girls reported significantly more symptoms of depression ( p  = .001). Adolescent male and female dependents at high-risk for eating disorders and adult obesity reported comparable levels of eating-related and psychosocial stress. Data are needed to elucidate how adolescent military dependents respond to intervention and whether sex moderates outcome. Highlights: Adolescent military dependents at risk for eating and weight concerns report similar levels of disordered eating attitudes. Adolescent dependents at risk for eating and weight concerns report similar levels of social adjustment and self-esteem. Female adolescent military dependents report higher symptoms of depression compared to their male counterparts.